POTENSI TERAPEUTIK NANOFORMULASI PUNICALAGIN DARI EKSTRAK DELIMA (Punica granatum) SEBAGAI TERAPI ADJUVAN KANKER PARU: TINJAUAN LITERATUR - Anrofa, Farah Nabilah; Muhammad, Fajrizqi Rahmandiar (ESSENTIAL: Essence of Scientific Medical Journal, 2026)
Introduction: Lung cancer is one of the leading causes of cancer-related death in Indonesia, with incidence and mortality rates continuing to rise. Conventional therapies such as chemotherapy, radiotherapy, and immunotherapy face challenges related to limited effectiveness, uneven accessibility, and systemic side effects. Punicalagin, derived from pomegranate extract, exhibits anticancer activity but is limited by low bioavailability. The development of a chitosan-based nanoformulation offers a solution to enhance the stability and targeted delivery of punicalagin, thereby positioning as a safe and effective adjuvant therapy for lung cancer. Discussion: Punicalagin, the primary polyphenolic compound found in pomegranate (Punica granatum) extract, exhibits anticancer activity through various mechanisms, including the induction of mitochondrial oxidative stress, cell cycle arrest at the G1 phase, and apoptosis via activation of both intrinsic and extrinsic caspase pathways. Moreover, punicalagin inhibits cancer cell migration and invasion by downregulating the activity of MMP-2 and MMP-9. However, its low bioavailability limits its therapeutic application. To overcome this, a nanoparticle-based delivery system using chitosan has been developed. Chitosan exhibits biocompatible, biodegradable, and mucoadhesive properties, which enhance stability, encapsulation efficiency, and targeted delivery to cancer cells. The combination of punicalagin with chitosan nanoparticles has demonstrated superior efficacy in reducing the viability of A549 lung cancer cells compared to the individual components, while also exhibiting selectivity for cancer cells without harming normal cells. Conclusion: Punicalagin encapsulated in chitosan nanoparticles holds enormous potential as an innovative adjuvant therapy for lung cancer. This formulation offers promise as a more effective, selective, and accessible alternative for lung cancer treatment in Indonesia.